Effect of applications of collagen ointments on the healing of purulent-necrotic ulcers of finger tissues in cows - Andenko Victor (EDP Sciences, 2021)
The purpose of the research was to obtain new experimental samples of collagen antiseptic ointments and to evaluate the effect of their use on the healing of purulent-necrotic ulcers of the finger tissues in cows. To achieve this goal, two experimental samples of collagen ointment were made: the first sample was a collagen analog of «Levomekol» ointment, and the second sample was a collagen ointment based on «Kemistep+» hoof sanitizer. The evaluation of the effect of their application on the healing of purulent-necrotic ulcers of the finger tissues was carried out in two experimental groups of sick animals with purulent-necrotic ulcers of the hoof crumb tissues of 7 heads each. In the first experimental group of animals, the first experimental sample of the ointment was applied, in the second - the second experimental sample. According to the results of scientific studies, it was found that the use of collagen ointment with the disinfectant «Kemistep+» on purulent-necrotic ulcers of crumb contributed to a decrease in their number. The epithelization index in the second experimental group compared to the first experimental group indicated a more positive effect of the use of collagen ointment with the disinfectant «Kemistep+» on the healing of purulent-necrotic ulcers of the finger tissues in cows than similar applications of the collagen analogue of the ointment «Levomekol».